ANALISIS HUBUNGAN SIKAP TERHADAP SAINS DENGAN KEMAMPUAN KOGNITIF SAINS FISIKA SISWA SLTP KAWASAN PESISIR (KECAMATAN PULAU MERBAU) - Kurnia, Nina; Zulirfan, Zulirfan; Sahal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The study was aimed to determine the level of attitudes toward student science, student’s cognitive abilities and determine the relationship between attitudes toward science with the cognitive ability of physics science students in grade VIII SLTP in coastal areas (Kecamatan Pulau Merbau). The survey method was used as research method. The data of attitude toward science of student’s was obtained from questionnaire scores. Meanwhile the data of student’s cognitive ability was obtained from the result of mid term test. The results showed that the attitudes toward science of VIII grade students in coastal areas (Kec. Pulau Merbau) were in high category. While the cognitive abilities of students were in the low category. After the significance test was done, there was no significant influence between attitude toward science students with cognitive ability of students in class VIII SLTP in coastal area (Kecamatan Pulau Merbau).Keywords: Attitudes towards science, cognitive ability